ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013 -2017 - Ivana Kalista Andala, 15.05.52.0328; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This research is conducted to analyze the factors of capital structures effect. The factors being analyzed included as independent variable which consist of profitability, liquidity, asset structure, company standard and business risk. The populations of this research are property firm and real estate that have been registered in to Indonesia Stock Exchange (BEI). The researcher uses purposive sampling method to take some exemplary samples of the data. There are 145 companies in total of the period 2013-2017, meanwhile the remaining samples have been naturalized to 131 companies. The type of the data used in this research is secondary data committed by using multiple linear regression type of analysis. The research shows that profitability and asset structure have no significant effect to the capital structure. The liquidity points to negative significant effect on capital structure, company size points and business risk to positive significant effect on capital structure.